Heteroaromatization with 4-phenyldiazenyl-1-naphthol. Part I: Synthesis of some new naphthopyrans and naphthopyranopyrimidines - Radini, Ibrahim Ali; Abd El-Wahab, Ashraf Hassan Fekry (European Journal of Chemistry, 2016)
Reaction of 4-phenyldiazenyl /or 4-(p-tolyldiazenyl)-1-naphthol (1) with various substituted α-cyanocinnamonitriles (2a-h) and ethyl α-cyanocinnamates (2i-p) afforded 2-amino-4-(aryl)-6-(phenyldiazenyl /or p-tolyldiazenyl)-4H-naphtho[1,2-b]pyrano-3-carbonitrile (3a-h) and ethyl 2-amino-4-(aryl)-6-(phenyldiazenyl /or p-tolyldiazenyl)-4H-naphtho[1,2-b]pyrano-3-carboxylate (3i-p). Reaction of compound 3a with Ac2O or PhCOCl and formic acid afforded N-acetylamino or N,N-dibenzoylamino and naphthopyranopyrimidine derivatives (4-8), respectively. The structures of these compounds were established on the basis of IR, UV, 1H NMR, 13C NMR, and MS data.